2016
DOI: 10.1039/c6sc01066k
|View full text |Cite
|
Sign up to set email alerts
|

Control of chemical reactivity by transition-state and beyond

Abstract: State-specific reaction dynamics is largely controlled by transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 141 publications
(134 reference statements)
1
57
0
Order By: Relevance
“…This surprising result contradicts the extended Polanyi rules but can be understood by the SVP model, which suggests that the vibrational modes have stronger coupling with the reaction coordinate at the transition state than the translational mode . This and other examples suggest that the SVP model is more general, particularly for reactions with more than three atoms …”
Section: Transition‐state Control Of State‐to‐state Reactivitymentioning
confidence: 76%
See 2 more Smart Citations
“…This surprising result contradicts the extended Polanyi rules but can be understood by the SVP model, which suggests that the vibrational modes have stronger coupling with the reaction coordinate at the transition state than the translational mode . This and other examples suggest that the SVP model is more general, particularly for reactions with more than three atoms …”
Section: Transition‐state Control Of State‐to‐state Reactivitymentioning
confidence: 76%
“…Both models are based on transition‐state properties, thus expected to work best when the reaction is controlled by the transition state. The SVP model has been applied to a number of reactions and the results have been quite promising . In Figure , the projections of reactant and product normal mode vectors onto the reaction coordinate at the transition state are shown for the prototypical X + H 2 O → HX + OH (X = H, F, Cl) reactions.…”
Section: Sudden Vector Projection Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the quasi‐classical trajectory method, the Guo group showed that for the OH + HCl reaction, the vibrational excitation of the HCl reactant greatly increases the reactivity, while the OH vibrational acts essentially as a spectator . This result was indicated as contradicting the Polanyi's rule, which suggests that the translational energy is more efficient than vibrational energy in enhancing an early barrier reaction: the authors elucidated this violation by a sudden vector projection model, which attributes the promotional effect of the HCl vibration mode to its strong coupling with the reaction coordinate at the transition state …”
Section: Introductionmentioning
confidence: 97%
“…[21] This result was indicated as contradicting the Polanyi's rule, which suggests that the translational energy is more efficient than vibrational energy in enhancing an early barrier reaction: the authors elucidated this violation by a sudden vector projection model, which attributes the promotional effect of the HCl vibration mode to its strong coupling with the reaction coordinate at the transition state. [21][22][23] The present approach Relevant from our view point are the quasi-classical trajectory calculations by Bonnet et al, [24] who demonstrated unexpected reaction pathways involving strong reorientation of the reagents, and showed that the most important channels were far from the minimum energy reaction path. They propose a dynamical extension of the notion of cone of acceptance to rationalize the stereodynamic effects.…”
Section: Introduction Experimental and Theoretical Backgroundmentioning
confidence: 99%